Antecedents of Green Warehousing: A Theoretical Framework and Future Direction - Siti Norida Wahab; Nazura Mohamad Sayuti; Mohamed Syazwan Ab Talib (International Journal of Supply Chain Management, 2018)
In todays competitive logistics environment, green and sustainable approaches are gaining academic interest. This paper aims to develop a theoretical framework to enhance understanding and academic knowledge on the antecedents of green warehouse practices (GWP). This paper employs content analysis approach to extract the potential factors to GWP. It then reviews and synthesises the GWP factors by applying two prominent management concepts of stakeholder and institutional theories. Through the review and discussion, six GWP factors; employee involvement, top management commitment, owner support, governmental pressure, industry competition, and customer demand are highlighted. Additionally, six propositions of GWP are presented and the framework developed in this conceptual paper underlines the internal and external GWP instigators. The conceptual nature of this paper offers a preliminary insights of GWP where the synergy between external and internal elements must coexist to successfully implement GWP. The developed theoretical framework presents a platform for future empirical GWP studies.